Carrier signal injection‐based sensorless control for permanent magnet synchronous machine drives with tolerance of signal processing delays. Issue 6 (1st July 2017) - Xu, Peilin; Zhu, Ziqiang
Abstract : In the case of high precision A/D converters, carrier signal injection based position estimation methods can adopt a relatively higher injection frequency (>1/10 pulse width modulation (PWM) switching frequency), which can lead to enhanced system bandwidths. However, simultaneously, signal processing delay effects (e.g., PWM duty ratio updating delay, etc.) become prominent, resulting in large phase shifts of carrier currents. On the other hand, the high frequency (HF) resistance effects may also be enlarged. Consequently, large oscillating position estimation errors will arise for the pulsating injection method due to carrier signal distortions induced by the delay and HF resistance effects. In order to suppress the undesirable position errors, based on the theoretical analyses, a new compensation strategy of maximizing the useful inductive saliency part and minimising the resistive saliency components using a PI regulator is proposed. The proposed position error suppression method is very easy and simple to implement, and moreover can significantly improve the sensorless control performance. Furthermore, the similar compensation strategy can also be applied for the position error compensation for rotating injection method as will also be discussed in this paper. Finally, the theoretical analyses and compensation effectiveness are validated by experiments on a laboratory interior permanent magnet machine.